Educational Values of Tolerance in the Quran: A Tarbawy Tafsir Perspective - Mansir, Firman; Rosele, Muhammad Ikhlas; Busahdiar, Busahdiar; Farihen, Farihen (UIN Syarif Hidayatullah Jakarta, 2024)
This study aims to explain the values of tolerance education in the Qur'an using the tarbawy interpretation approach. Discrimination in social life and the world of education must be eroded so that no one feels better and degrades one another. The results showed that the values of tolerance education are repeatedly mentioned in the Qur'an. This verse's affirmation leads to maintaining differences, respect between religions, and brotherhood because humans are created with different forms to realize unity and know each other. This can also be realized in the world of education between students and other students, teachers and students, and vice versa. The research method used is qualitative in collecting primary and secondary data through a literature analysis process. The data collected are the Ministry of Religion's version of the Qur'an, international and national journals, and several books that are the results of research on tolerance education. Thus, the values of democratic education can create a harmonious life in educational institutions, prosperous and prosperous, without discrimination and dichotomization, respecting each other by building strength together so as to achieve mutual prosperity and a harmonious life.